Preparasi dan Karakterisasi Nanopartikel Kitosan-Naringenin dengan Variasi Rasio Massa Kitosan-Natrium Tripolifosfat (Preparation and Caracterization of Naringenin-Chitosan Nanoparticles with Various Mass Ratio of Chitosan-Sodium Tripolyphosphat) - Helmi Nur Laili; Lina Winarti; Lusia Oktora Ruma Kumala Sari (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Naringenin has a wide pharmacological activities. Low bioavailability of naringenin caused the under-developed utilization. Preparation of naringenin nanoparticles can improve the bioavailability. Chitosan as polymer for nanoparticles has ideal properties such as nontoxic, biocompatible, biodegradable. Sodium tripolyphosphat (NaTPP) used as an crosslinker to form nanoparticles by ionic gelation method. The aim of this research is to know the optimum formula of chitosan and NaTPP in naringenin-chitosan nanoparticles based on entrapment efficiency (EE) using factorial design. In this research, naringenin-chitosan nanoparticles were prepared with various mass ratio, 6:1, 10:1, 3:1, 5:1 and then EE each formulas measured by UV spectrophotometer. The optimum formula of naringenin-chitosan nanoparticles were characterized by PSA, TEM, and FTIR. The optimum formula (3:1) showed EE >42.12%. The consentration of chitosan and NaTPP to get final optimum formula were 0.06-0.0606777% for chitosan and 0.0970833-0.1% for NaTPP. The result of characterizations showed that size of naringenin-chitosan nanoparticles 13.2 ± 2.6 nm, PDI 0.443, zeta potensial 15.23 mV, complex chitosan-TPP formed. The results demostrated naringenin nanoparticles have successfully prepared. Keywords: naringenin, nanoparticle, chitosan, sodium tripolyphosphat